Lead and mercury variability in three Italian lakes spanning the last 10,000 years: trends and relation with anthropic factors - Francesca Pasquetti; Benoît Caron; Julie Noel; Michel Magny; Scott A. Mensing; Gianluca Piovesan; Monica Bini; Giovanni Zanchetta (Journal of Paleolimnology, 2026)

Reconstruction of climatic and socio-economic impacts on the landscape of Northern Tuscany (Italy) over the last 2000 years based on palaeoecological and historical evidence - Scott Mensing; Theodore Dingemans; Edward Schoolman; Gianluca Piovesan; Adam Csank; Paolo Tomei; Simone Maria Collavini; Annamaria Pazienza; Federico Cantini; Jordan Palli; Giovani Zanchetta; Monica Bini (Anthropocene, 2025)

The human-driven ecological success of olive trees over the last 3700 years in the Central Mediterranean - Jordan Palli; Sabina Fiolna; Monica Bini; Federico Cappella; Adam Izdebski; Alessia Masi; Scott Mensing; Lorenzo Nigro; Gianluca Piovesan; Laura Sadori; Giovanni Zanchetta (Quaternary Science Reviews, 2025)

The Paleo‐Serchio River: history of floods between Lucca and Pisa during the Roman period - Monica Bini; Alberto Caroti; Federico Cantini; Fabio Fabiani; Marco Fiorentini; Antonio Fornaciari; Ilaria Isola; Marco Lazzarotti; Marco Luppichini; Scott Mensing; Jordan Palli; Gianluca Piovesan; et al. (Journal of Quaternary Science, 2025)
The reconstruction of flood frequency beyond the Instrumental Era is challenging and mostly based on historical sources, but it rarely covers more than the last 1000 years when abundant documentation is preserved. To investigate the long‐term trends in flooding and obtain insight into current climatic changes it is necessary to extend these data to a larger number of rivers beyond the Instrumental Era and available period of historical documentation. In this paper we reconstruct the paleoflood record for the Roman Period of the Serchio River ( Auser in antiquity, located in Northern Tuscany, Central Italy) using geoarcheological data. The complex hydrological evolution of the river and the development of the important cities of Lucca and Pisa on the river bank allowed an important collection of data, showing a prominent peak in flood activity during the 1st century ce , which seems to correspond to an increase in regional rainfall interpreted from speleothem proxies. A secondary peak is present in the 6th century ce , which corresponds locally with an increase in precipitation recorded by speleothems. The phases of increased flooding, when compared with present‐day synoptical meteorological conditions, probably developed during a period of negative North Atlantic Oscillation (NAO) Index, and it is partially supported by comparison with paleoproxies for NAO. These findings confirm that an extensive collection of geoarcheological data, supported by geological and geomorphological investigation, represents a powerful tool to be integrated with historical data for the reconstruction of floods. The concomitance of local paleohydrological proxies can help in disentangling the origin of the signal from other causes.

The recent evolution of the salt marsh ‘Pantano Grande’ (NE Sicily, Italy): interplay between natural and human activity over the last 3700 years - Jordan Palli; Lorenzo Monaco; Monica Bini; Emanuela Cosma; Biagio Giaccio; Adam Izdebski; Alessia Masi; Scott Mensing; Gianluca Piovesan; Veronica Rossi; Laura Sadori; Bernd Wagner; et al. (Journal of Quaternary Science, 2024)
Combined natural processes and human activities shaped the late Holocene landscape history in many Mediterranean regions. This is especially true with areas subjected to specific human interest, such as coastal areas morphologically suitable to the establishment of harbours. Here, we test the hypothesis on the location of the Roman harbour Portus Trajectus in Peloro Cape (NE Sicily, Italy) and describe the evolution of the area over the last 3700 years through lithostratigraphic, geochemical, meiofauna and microfossil analyses performed on a new sediment core recovered from the coastal salt marsh Pantano Grande (aka Lago di Ganzirri ). The age–depth model was developed on radiocarbon dates and geochemical fingerprinting of two tephra layers. Results indicate that the area underwent dramatic changes ca . 650 bce. The anthropogenic impact of Greek colonies may have contributed to modifying the coastal environment of Peloro Cape due to their widespread impact on natural resources. This happened at many localities in the Mediterranean, indicating the magnitude of impact of the Greek colonies over the landscape. According to our results, it is unlikely that the current Pantano Grande basin was used as a harbour in Roman times, although the presence of a harbour in the nearby Pantano Piccolo marsh cannot be excluded. Pantano Grande had been isolated from the sea for more than 2000 years. Human intervention in the 19 th century halted that isolation and provided the background for the ecological, economic and social functions the salt marsh performs today.

Temporal and geographic extent of the late Holocene dry period in the central Great Basin, USA - Scott Mensing; Wei Wang; David Rhode; Douglas J. Kennett; Adam Csank; David Hurst Thomas; Cedar Briem; Thomas K. Harper; Brendan J. Culleton; Richard J. George; John Southon (Quaternary Science Reviews, 2023)

The potential of paleoecology for functional forest restoration planning: lessons from Late Holocene Italian pollen records - Gianluca Piovesan; Anna Maria Mercuri; Scott A. Mensing (Plant Biosystems, 2018)

Pre‐mission invasion of Erodium cicutarium in California - Scott Mensing; Roger Byrne (Journal of Biogeography, 1998)
The California grassland is dominated by alien plant species. It is generally assumed that the invasion of aliens began with the initial introduction of livestock by Spanish missionaries in 1769. In this paper we present pollen evidence which indicates that Erodium cicutarium , a Mediterranean annual, was well established in the Santa Barbara region several years before the founding of the first California mission at San Diego in 1769. Historical evidence shows that it took the Spanish nearly a decade to develop a livestock base in California. Disturbance by livestock was therefore not a necessary prerequisite for invasion by alien plants. Historical and macrofossil evidence indicates that E. cicutarium invaded California from Baja California.